Transanal minimally invasive surgery for total mesorectal excision (ETM) through transanal approach (TaETM) with robotic and Transanal Endoscopic Operations (TEO) combined access: step by step surgery - MENDES,Carlos Ramon Silveira (2015)
RATIONAL: In the treatment of colorectal cancer, from 1982 Heald proposed standardization of the total mesorectal excision, with a significant reduction in the recurrence rate. But the treatment of lower rectal lesions is still a challenge. AIM: To describe the association of robotic low anterior resection- TATA (Transanal Abdominal Transanal Resection), with transanal access using Transanal Endoscopic Operations - TEO in the treatment of lower rectal cancer. METHOD: The TATA performs robotic abdominal approach and the TEO performs the perineal approach, developing total mesorectal excision (TME) transanally (TaETM). RESULT: The TaETM technique was applied in a woman with rectal adenocarcinoma 5 cm from the anal verge that had been submitted to chemoradiation. The procedure was performed with satisfatory operative time and favorable oncological outcome (grade 3 mesorectal excision). CONCLUSION: This is a promising minimally invasive procedure in the armamentarium of rectal cancer treatment, specially in challenging scenarios such as narrow pelvis, obesity and very low rectal tumors.